Pure Gamai Enterprise - Ab. Rosdy, Merhanah; Sappari, Noraasyiqin; Arisa, Sadzlena; Harunsah, Afa Nurul Fatiha; Mujim, Nurizan (2014)
PURE GAMAI ENTERPRISE is a partnership company that organizes by five members of partner which is Afa Nurul Fatihah as the operational manager, Nur Asyiqin as the admin manager, Sadzlena as the marketing manager, Nurizan the financial manager and the last one Merhanah as the general manager. This business is focus on producing a seaweed powder from the pure seaweed whereby the seaweed supply we got from our own farm which is we plant and harvest the seaweed to get the material in order to produce the pure seaweed powder. The seaweed are highly demand nowadays in the market and the seaweed was extract to produces the Carrageenan. Whereby carrageenan is used for many manufacture industries such as the cosmetic and the most important is in food industries which is pure seaweed powder. For the first step is, our company will produce the fresh seaweed which is we farming the seaweed and then, harvest it to the next procedure which is drying in order to send the raw material to the rent factory and produce the pure seaweed powder. Besides that, the less number of competitors in seaweed industry and high demands from the people also give this company chances to develop the company economy with more firm. And the fact, these industries also play an important role in order to challenge the Sabah development Corridor objectives. At the same time, the Sabah government also gives support to the private companies to modernize and develop the seaweed industry. Although this company is a new in this industry and lack of experiences but with the helps and encouragement from local government, we believe that this industry can give a benefit and high profit to our company and at the same time can develop the national economy. In a nutshell, the reason why we choose seaweed is because of the high demand from the people and less competition especially there are only a few person that produce powder from seaweed and the facts, Malaysia is the best quality of seaweed production. At the same time, we also have notice that seaweed have many benefits in term of our health that have been prove by the scientist whereby seaweed can overcomes poor digestion, increases metabolism and many else. The most important things is, seaweed also can be used in term of production such us produce a plastic, for beauty which is produce a collagen and the last is for food such as powder from the seaweed which is our company product.